Plasmonic Ag/Cu/PEG nanofluids prepared when solids meet liquids in the gas phase - Biliak, Kateryna; Nikitin, Daniil; Ali-Ogly, Suren; Protsak, Mariia; Pleskunov, Pavel; Tosca, Marco; Sergievskaya, Anastasiya; Cornil, David; Cornil, Jérôme; Konstantinidis, Stephanos; Košutová, Tereza; ernochová, Zulfiya; et al. (Nanoscale advances, 2023)
Since the time of Faraday's experiments, the optical response of plasmonic nanofluids has been tailored by the shape, size, concentration, and material of nanoparticles (NPs), or by mixing different types of NPs. To date, water-based liquids have been the most extensively investigated host media, while polymers, such as poly(ethylene glycol) (PEG), have frequently been added to introduce repulsive steric interactions and protect NPs from agglomeration. Here, we introduce an inverse system of non-aqueous nanofluids, in which Ag and Cu NPs are dispersed in PEG (400 g mol −1 ), with no solvents or chemicals involved. Our single-step approach comprises the synthesis of metal NPs in the gas phase using sputtering-based gas aggregation cluster sources, gas flow transport of NPs, and their deposition (optionally simultaneous) on the PEG surface. Using computational fluid dynamics simulations, we show that NPs diffuse into PEG at an average velocity of the diffusion front of the order of μm s −1 , which is sufficient for efficient loading of the entire polymer bulk. We synthesize yellow Ag/PEG, green Cu/PEG, and blue Ag/Cu/PEG nanofluids, in which the color is given by the position of the plasmon resonance. NPs are prone to partial agglomeration and sedimentation, with a slower kinetics for Cu. Density functional theory calculations combined with UV-vis data and zeta-potential measurements prove that the surface oxidation to Cu 2 O and stronger electrostatic repulsion are responsible for the higher stability of Cu NPs. Adopting the De Gennes formalism, we estimate that PEG molecules adsorb on the NP surface in mushroom coordination, with the thickness of the adsorbed layer L < 1.4 nm, grafting density σ < 0.20, and the average distance between the grafted chains D > 0.8 nm. Such values provide sufficient steric barriers to retard, but not completely prevent, agglomeration. Overall, our approach offers an excellent platform for fundamental research on non-aqueous nanofluids, with metal-polymer and metal-metal interactions unperturbed by the presence of solvents or chemical residues. Yellow, green, and blue plasmonic nanofluids were produced without wet chemistry by direct deposition of Ag, Cu, and simultaneous co-deposition of Ag + Cu nanoparticles from sputter-based gas aggregation cluster sources in liquid polyethylene glycol.